What discourse analytic approaches contribute to the study of language and autism. (15th June 2017) - Sterponi, Laura; de Kirby, Jenton
Abstract : In this article, we offer a framework for conceptualizing the contribution of discourse analytic approaches to the study of the verbal communication of children with autism, with an emphasis on conversation analysis. We argue that insights from these approaches serve to complexify traditional deficit interpretations of prototypical features of autistic language, such as pronoun atypicality, pragmatic difficulties, and echolalia. Our framework is presented in three parts, each comprising a theoretical premise about language made by discourse analytic approaches and the premise's methodological corollary. To illustrate, we analyze extracts from three children with autism, pointing to competencies and interactional processes and that are largely invisible in mainstream research. Finally, we describe how these insights offer fruitful suggestions for clinical intervention.